(3OhQ GddYH GdJQHhj aj JYRjR Gdbje GdLeGdjI HQjGV GdGWaGds - (3eYfi, gjGes ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2015)
(3JgOa GdOQGSI Edi GdJYQa Ydi OhQ GddYH GdJQHhj aj JYRjR Gdbje GdLeGdjI HQjGV GdCWaGd, hJSYi deYQaI eOi JWHjb GdHQGeL GdJQHhjI Vef GdeOGQS, hGdJYQa Ydi OhQ GdMGObI aj HfGA TNUjI GdWad hGdJCcO ef JcQjSgG hbJ deeGQSI GddYH GdJQHhj aj Gdjhe, hGdSYj deYQaI eOi GSJNOGe GddYH GdJQHhj aj EjUGd GdeaGgje hGdbje, HGdEVGaI Edi GdJYQa Ydi Cge Gdbje GdLeGdjI hGdhSGFd hGdCOhGJ GdJj jJe JYRjRgG YfO GdWad(B. (3CYJeOJ GdOQGSI GdefgL GdhUaj (B- (3GdJMdjdj, aGbJUQJ GdOQGSI Ydi NeS eOGQS QSejI hNGUI eJfhYI GdWhGFa aj eMGaXI GdLfhH bVGA UhQ, TedJ GdYjfI (B150 (3WadkG aj QjGV GdCWaGd JJQGhM CYeGQge Hjf KdGK Edi SJ SfhGJ, h(B40 (3ef MGObGJ GdQjGV(B. (3ESJNOeJ COGI GdESJeGQI, GdebGHdI hGdedGMXI(B. (3HjfJ GdfJGFL aQhbGJ hJaGhJkG YfO GSJNOGe GddYH GdJQHhj aj JTcjd TNUjI GdWad, hJfejI GdbOQGJ GdYbdjI hGdMhGS, hJRhjOg HGdNHQGJ GdJj JHfj TNUjJg(B. (3hJHjf HYV GdeTGcd aj JCgjd GdMGObGJ JCgjdkG JQHhjkG deYQaI OhQ GddYH GdJQHhj aj JQHjI GdCWaGd, hYOe hLhO hYj cGed dOjge HCgejI afhf GdCWaGd aj JTcjd TNUjGJge, hYOe eYQaI eYXege Heaghe Gdbje GdLeGdjI heYfGgG, hGYJeGOge HTcd LRFj Ydi GdcJGH(B. (3hJHjf JaGhJkG aj JYRjR Gdbje GdLeGdjI aj GdHQGeL hGdWQb, hZjGH cdj dbSe GdJQHjI GdeNJUI GdPj jYed Ydi eQGYGI GdaQhbGJ GdaQOjI HGdefGgL hGdWQb(B. (3de jXgQ GdOhQ GdaYdj GdPj jDOjg GddYH GdJQHhj hGSJNOGeGJg aj JYRjR Gdbje GdLeGdjI, Vef GdfXQjGJ GdJQHhjI ddYH hecGfI GddYH GdJQHhj aj GdacQ GdYQHj hGdESdGej, hYdGbJg hahGFOg aj JYRjR Gdbje GdLeGdjI aj QjGV GdCWaGd(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Jouer et jeux; Kindergarten; Maternelle; Valeurs et Education; Values and Education Play and games; (3GdJYdje hGdbje GddYH hGdGdYGHs; (3QjGV GdCWaGds